AUV 3D Path Planning Based on A Algorithm - Li, Mengchuan; Zhang, Huajun (Chinese Automation Congress (Online), 2020)
Aiming at the problem of global static path planning in the submarine terrain environment of autonomous underwater vehicle(AUV),A three-dimensional environment model was built based on gridmethod, and Dijsktra algorithm and A* algorithm were used to realize three-dimensional path search. The simulation results show that the search time of the two algorithms is shorter, but the A* algorithm is better than Dijsktra algorithm in terms of the number of nodes and path length.A multi-direction A* algorithm is designed to reduce the number of search nodes and further shorten the search path. AUV 3d path planning has high efficiency and real-time performance.